The Times They Are a-Changin': Carbapenems for Extended-Spectrum-β-Lactamase-Producing Bacteria - Rodríguez-Baño, Jesús (Antimicrob Agents Chemother, 2015)
Several antimicrobial agents are being investigated as alternatives to carbapenems in the treatment of infections caused by ESBL-producing Enterobacteriaceae, which may be useful in avoiding overuse of carbapenems in the context of recent global spread of carbapenem-resistant Enterobacteriaceae. The most promising candidates for invasive infections so far are β-lactam/β-lactamase inhibitor combinations and cephamycins.